GPR87 Is an Overexpressed G-Protein Coupled Receptor in Squamous Cell Carcinoma of the Lung. Issue 1 (2008) - Gugger, Mathias; White, Richard; Song, Susan; Waser, Bea; Cescato, Renzo; Rivière, Pierre; Reubi, Jean Claude
Abstract : Lung cancer is the leading cause of cancer death worldwide. The overall 5-year survival after therapy is about 16% and there is a clear need for better treatment options, such as therapies targeting specific molecular structures. G-protein coupled receptors (GPCRs), as the largest family of cell surface receptors, represent an important group of potential targets for diagnostics and therapy. We therefore used laser capture microdissection and GPCR-focused Affymetrix microarrays to examine the expression of 929 GPCR transcripts in tissue samples of 10 patients with squamous cell carcinoma and 7 with adenocarcinoma in order to identify novel targets in non-small cell lung carcinoma (NSCLC). The relative gene expression levels were calculated in tumour samples compared to samples of the neighbouring alveolar tissue in every patient. Based on this unique study design, we identified 5 significantly overexpressed GPCRs in squamous cell carcinoma, in the following decreasing order of expression: GPR87 > CMKOR1 > FZD10 > LGR4 > P2RY11. All are non-olfactory and GRAFS (glutamate, rhodopsin, adhesion, frizzled/taste2, secretin family) classified. GPR87, LGR4 and CMKOR1 are orphan receptors. GPR87 stands out as a candidate for further target validation due to its marked overexpression and correlation on a mutation-based level to squamous cell carcinoma.